Hubungan Aktivitas Fisik dan Pola Makan dengan Indeks Massa Tubuh Mahasiswa Keperawatan - Ulan Prisilia; Evelin Malinti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between physical activity and eating patterns on the body mass index of nursing students. The method used is the analytical observation method with a cross-sectional approach. The results showed that physical activity had a p-value> 0.05 and diet had a p-value> 0.05. In conclusion, there is no significant relationship between physical activity and body mass index, and there is no relationship between diet and body mass index. Keywords: Physical Activity, BMI, Nursing Students, Diet